Advances in DNA methylation and its role in cytoplasmic male sterility in higher plants - Atiqur Rahman; Md. Hasan Sofiur Rahman; Md. Shakil Uddin; Naima Sultana; Shirin Akhter; Ujjal Kumar Nath; Shamsun Nahar Begum; Md. Mazadul Islam; Afroz Naznin; Md. Nurul Amin; Sharif Ahmed; Akbar Hossain (Journal of Integrative Agriculture, 2024)
The impact of epigenetic modifications like DNA methylation on plant phenotypes has expanded the possibilities for crop development. DNA methylation plays a part in the regulation of both the chromatin structure and gene expression, and the enzyme involved, DNA methyltransferase, executes the methylation process within the plant genome. By regulating crucial biological pathways, epigenetic changes actively contribute to the creation of the phenotype. Therefore, epigenome editing may assist in overcoming some of the drawbacks of genome editing, which can have minor off-target consequences and merely facilitate the loss of a gene’s function. These drawbacks include gene knockout, which can have such off-target effects. This review provides examples of several molecular characteristics of DNA methylation, as well as some plant physiological processes that are impacted by these epigenetic changes in the plants. We also discuss how DNA alterations might be used to improve crops and meet the demands of sustainable and environmentally-friendly farming.